The aftermaths of lowering the school leaving age: Effects on Roma youth - János Köllő; Anna Sebők (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
In 2013, the Hungarian government cut the school leaving age from 18 to 16. We study the impact of this unique reform on the country's sizeable Roma minority using census data on the universe of 17-year-olds in 2011 and a 10 percent random sample in 2016. School attendance fell by more than 20 percentage points among Roma youth as opposed to less than 6 points with their non-Roma counterparts. Roma's post-reform drawbacks in school enrolment were predominantly explained by their family background, neighborhood characteristics, and, much less importantly, below-average school performance. Changes in local employment prospects had no remarkable impact on the post-reform ethnic gap. More stringent selection and self-selection by social status and school performance (rather than ethnicity) nevertheless affected the Roma minority disproportionally, with close to 30 percent of their 17-year-old children being out of education, training, and employment three years after the reform.
Keywords: I24; J15; J48; 330; school leaving age; Roma; Hungary